Basic concepts on rheology and application of shear-thickening fluids in protective gear - Cossa, K.N. (Springer Nature, 2019)
The current manuscript aims to describe and introduce the nature of the fluids that are usually observed in the environment and a brings the suggestion on how dilatant fluids can be applied for protective gear. It explains how these fluids influence in the equipment and why it is a good idea to use them for such situations. In the study of fluid mechanics, the fluid is the main important component to be taken into account, however, it can be classified as Newtonian and non-Newtonian fluid. It is important to understand the behaviour of such fluids so that one can predict the alterations and their responses under various conditions. Newtonian and non-Newtonian fluids have very different characteristics and the following study focuses on underlying the similarities and discrepancies. The discipline called Rheology is the one that focuses on these types of fluids and the deformation that they go through when stresses are applied. The term can be divided in ârheoâ, which has origins from Greek and means flow and âlogiaâ, which means study of. Therefore, Rheology means study of flow. It has focused majorly in the study of fluids, however, lately, there has also been some focus on the study of deformation of solids and some other substances that are called viscoelastic materials 8, 9, 13. By understanding the rheology of the dilatant fluids, it was possible to understand the benefits that the use of this fluids can offer when there is a need in the society, such as to improve the efficiency and efficacy of the body armours. In engineering, it is important to find solutions to issues that are observed in the society and facilitate the processes, advising for improvements that make humansâ lives easier. The main issue in cause here is that the already existent body armours are, first too heavy, because there has been need to compensate with weight, to improve the protection and they are not effective in protecting the person who wears them from the impact, many times bruises being cause in the process and people remaining with some type of pain after the impact. This study is important for suggesting an alternative, which are the liquid body armours, with use of shear-thickening fluids in their constitution. The explanations regarding the impact of stresses on such materials and the suggested applications are presented in the next pages of this paper. Â© 2019, Springer Nature Switzerland AG.